2019
DOI: 10.1016/j.stemcr.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Brain Capillary-like Endothelial Cells from Human Pluripotent Stem Cell-Derived Endothelial Progenitor Cells

Abstract: SummaryThe derivation of human brain capillary endothelial cells is of utmost importance for drug discovery programs focusing on diseases of the central nervous system. Here, we describe a two-step differentiation protocol to derive brain capillary-like endothelial cells from human pluripotent stem cells. The cells were initially differentiated into endothelial progenitor cells followed by specification into a brain capillary-like endothelial cell phenotype using a protocol that combined the induction, in a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 48 publications
6
67
0
Order By: Relevance
“…While EECM-BMEC-like cells have weaker barrier properties than UMM-or DMMdifferentiated BMEC-like cells, they are similar to other human stem cell-derived models 15,18,51 and primary mouse BMECs, 61,62 and have stronger barrier properties than immortalized human or rodent cell lines. 10,50,63 EECM-BMEClike cells are similar to recently reported hiPSC-derived brain capillary-like endothelial cells (BCLECs) 18 as both proceed through an EPC intermediate and develop a moderate TEER of ~60-80 Ω × cm 2 . However, in contrast to the work of Praça et al 18 we found that EECM-BMEC-like cells demonstrated pro-inflammatory cytokine-inducible expression of VCAM-1, a prerequisite for studying immune cell interactions with the BBB.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…While EECM-BMEC-like cells have weaker barrier properties than UMM-or DMMdifferentiated BMEC-like cells, they are similar to other human stem cell-derived models 15,18,51 and primary mouse BMECs, 61,62 and have stronger barrier properties than immortalized human or rodent cell lines. 10,50,63 EECM-BMEClike cells are similar to recently reported hiPSC-derived brain capillary-like endothelial cells (BCLECs) 18 as both proceed through an EPC intermediate and develop a moderate TEER of ~60-80 Ω × cm 2 . However, in contrast to the work of Praça et al 18 we found that EECM-BMEC-like cells demonstrated pro-inflammatory cytokine-inducible expression of VCAM-1, a prerequisite for studying immune cell interactions with the BBB.…”
mentioning
confidence: 61%
“…For immune cell studies, one could also envision combining hiPSC and autologous immune cells sourced from the same patient cohort. Human iPSC-derived in vitro models of the BBB have been established 14,[16][17][18] and proven useful for modeling BBB dysfunction in inheritable neurological disorders in vitro. [19][20][21] Presently available hiPSC-derived in vitro BBB models are well characterized with respect to their barrier properties and expression of BBB-specific transporters and efflux pumps 14,16,17 and have proven useful for the study of barrier regulation, molecular transport, and brain drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Most relevant to this commentary, induction and maintenance of endothelial character with a corresponding reduction of epithelial character continues to be a goal. Factors such as hypoxia [19], shear stress [9,19], and three dimensional architecture [10,28,29] have been suggested to increase vascular character, and other models based on induction of BBB character in generic hiPSC-derived ECs are beginning to emerge [32]. Despite these advances, we believe it is prudent to exercise caution when utilizing hPSC-derived BMEC-like cells for studies where the endothelial phenotype is crucial.…”
Section: Main Textmentioning
confidence: 99%
“…The development of stem cell-based technologies opened up a new opportunity to generate human in vitro BBB models. Induced pluripotent stem cells (iPSCs)-derived brain-like endothelial cells (BLECs) can be obtained by specific differentiation protocols [4][5][6][7][8][9][10][11]. Another published method is the use of umbilical cord blood-derived hematopoietic stem cells for differentiation into endothelial cells, followed by the induction of BBB properties by co-culture with brain pericytes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%